ANALYSIS OF TEACHERS DIFFICULTIES IN AUTHENTIC ASSESSMENT OF MATHEMATICS LEARNING DURING THE PANDEMIC COVID-19 - Yuni Nurherliyani; Nani Ratnaningsih (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2022)
The study aims to analyze the difficulties of teachers in authentic assessment of mathematics during the pandemic. Authentic assessment includes knowledge assessment, attitude assessment, and skills assessment. This study used a qualitative research with a descriptive design. The sample of this research is 100 mathematic teachers in Tasikmalaya City. Data collection techniques in this study by questionnaires. Analyzed using the concept of Miles and Huberman through reduction, data display and conclusion. The results showed that the difficulties of authentic assessment in mathematics learning include requiring intensive time, making assessment impractical, difficulties in developing teaching materials, and difficulties in planning the type of assessment.